A systematic review of the use of quality‐of‐life instruments in randomized controlled trials for psoriasis. (1st March 2017) - Ali, F.M.; Cueva, A.C.; Vyas, J.; Atwan, A.A.; Salek, M.S.; Finlay, A.Y.; Piguet, V.
Summary: Planners of interventional studies in psoriasis face the dilemma of selecting suitable quality‐of‐life (QoL) measures. Systematic reviews have the potential of identifying psychometrically sound measures in a given therapeutic area, while guiding the development of practice guidelines. The aim of this systematic review was to generate evidence of the use of QoL instruments in randomized controlled trials (RCTs) for interventions in psoriasis. The methodology followed the PRISMA guidelines. Six databases were searched with 388 search terms. Abstracts of articles were reviewed independently by two assessors, and a third adjudicator resolved any opinion differences. Risk of bias was assessed using the Jadad scale. Of 3646 screened publications, 99 articles (100 trials) met the eligibility criteria for inclusion, describing research on 33 215 patients. Thirty‐three trials tested topical therapy, 18 systemic, 39 biologics, nine phototherapy and 10 other interventions. The Dermatology Life Quality Index (DLQI) was the most commonly used QoL instrument (83 studies, 83%), followed by the 36‐Item Short Form Survey (SF‐36) (31, 31%), EuroQoL‐5D (EQ‐5D) (15, 15%), Psoriasis Disability Index (14, 14%) and Skindex (five, 5%). There was widespread inconsistency in the way that QoL data were reported. Of the 100 trials identified, 37 reported minimal clinically important difference (MCID): 32 for DLQI, 10 for SF‐36 and six for EQ‐5D. QoL measurement is increasingly being reported in RCTs of psoriasis. Formal guidelines are needed for assessment and publishing of QoL data. Researchers should consider whether MCID information is available, and development of MCID data should be encouraged.